Pledging Engagement: Motivations and Intentions for College Sport Attendance among Greek-Letter Organizations - Stacey A. Forsythe; Alison Fridley; Chris Corr; Sarah Stokowski; Nnamdi Ezike (Journal of Applied Sports Management, 2023)
While ticket sales and revenue have remained relatively constant in collegiate athletics over the past decade, attendance has steadily declined. Given the range of entertainment options available, student attendance at collegiate athletic events has, specifically, declined. While athletic administrators are often revenue oriented, decreasing attendance has effects that span campus communities and cultures. As Greek-letter organizations are nearly ubiquitous within the higher education setting, fraternity and sorority members serve a unique opportunity area for engagement with fan attendance initiatives and future alumni giving. Accordingly, this study examined the motivations for attending collegiate athletic events as a member of a Greek-letter organization and the intention to attend collegiate athletic events as an alumnus of a Greek-letter organization. Findings illustrate that students and alumni that are affiliated with Greek-letter organizations have greater motivation to attend collegiate athletic events as students and greater intention to attend collegiate athletic events as alumni.
Keywords: sport consumption behavior; sport attendance; Greek-letter organizations; alumni engagement